PENAPISAN DAN PEMANFAATAN RHIZOBAKTERI TANAMAN SORGUM (Sorghum bicolor L. Moench) SEBAGAI INOKULAN PEMACU TUMBUH TANAMAN - Annisaa Widyasari; W Wijanarka; Budi Raharjo; Mamik Setyowati (Departemen Biologi, Fakultas Sains dan Matematika Undip, 2016)
Sorghum was a cereal crop that has many benefit such as food, feed, industrial, and bioenergy. Sorghum had a potency to be cultivated, but productivity of sorghum was still low both in quatity and quality. One way to increase production of sorghum is using rhizobacteria as biofertilizer. The aim of this study is to get rhizobacteria that has the ability to produce IAA, solubility of phospat (P), Nitrogen (N) fixing, and analyze the effect of rhizobacteria inoculants for enhance sorgum plant growth. Isolation of rhizobacteria was done by diluting rhizobacteria sorghum suspension from 10-1 to 10-5 and it were be platted on SEA medium. Isolates were screened by ability to produce IAA, solubility of P, and N fixing. Producing of IAA test was done by adding Salkowsky reagent on bacterial supernatant and measured absorbance at 530 nm wavelength. Solubility of P test was done by inoculating isolates in Pikovskaya media, while N fixing test was done on N fixing media (NFB). Isolates of rhizobacteria which had a potency to increase growth of plants were made inoculants to be applied in sorghum plants. The result of this study obtain 3 isolates i.e Sr 194.3; Sr 172.1; and Sr 209.1 which were considered effective for increase growth of sorghum. The conclusion of this study isolates which showed the highest average plant height, root length, and dry weight Sr 194.3 isolate. The statistical analysis among the treatments showed that did not any significant differences on plant height, root length, and dry weight of sorghum age 28 days after farming. Keyword : Increase growth plants, Screening, Shorgum, Rhizophere.